Recipe for tired teachers / Tengku Intan Suzila Tengku Sharif, Mohd Yusri Mohamad Noor and Azlini Razali - Tengku Sharif, Tengku Intan Suzila; Mohamad Noor, Mohd Yusri; Razali, Azlini (2004)
Over the past conferences held by UiTM, the purposes and aims is nothing more than just to create an opening ground for new breed of researchers in academic excellence. They have preached and argued over the ultimate essence of research production. Quantity of research production is at stake, however, many fusses as quality is uphold or merely unmotivated by the constant urge for number but not pure excellence. This conceptual paper addresses the issue and seeks solution and motivation to the frustration over satisfaction in the true scholarship of the teaching profession itself.